2014
DOI: 10.1177/0004563214530677
|View full text |Cite
|
Sign up to set email alerts
|

Chylothorax diagnosis: can the clinical chemistry laboratory do more?

Abstract: Background: Chylothorax is a rare anatomical disruption of the thoracic duct associated with a significant degree of morbidity and mortality. Diagnosis usually relies upon lipid analysis and visual inspection of the pleural fluid. However, this may be subject to incorrect interpretation. The aim of this study was to compare pleural fluid lipid analysis and visual inspection against lipoprotein electrophoresis. Methods: Nine pleural effusion samples suspected of being chylothorax were analysed. A combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Additionally, the thoracic fluid collected in each cat at each time point had a fluid cholesterol to triglyceride ratio of less than 1, further supporting the classification of the fluid collected as normal lymphatic fluid. 25,26 There was little deviation outside the normal reference range for the systemic values evaluated in this study (cholesterol, triglycerides, PCV, total protein and lymphocyte count) with the exception of relatively mild changes in PCV, triglycerides, and lymphocyte count. It is likely that the mild elevation in PCV seen in two cats on day 3 and one cat on day 9 (50%, 51% and 53%) was due to mild dehydration as those cats also had total protein values in the high end of the normal range.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Additionally, the thoracic fluid collected in each cat at each time point had a fluid cholesterol to triglyceride ratio of less than 1, further supporting the classification of the fluid collected as normal lymphatic fluid. 25,26 There was little deviation outside the normal reference range for the systemic values evaluated in this study (cholesterol, triglycerides, PCV, total protein and lymphocyte count) with the exception of relatively mild changes in PCV, triglycerides, and lymphocyte count. It is likely that the mild elevation in PCV seen in two cats on day 3 and one cat on day 9 (50%, 51% and 53%) was due to mild dehydration as those cats also had total protein values in the high end of the normal range.…”
Section: Discussionmentioning
confidence: 61%
“…Additionally, the thoracic fluid collected in each cat at each time point had a fluid cholesterol to triglyceride ratio of less than 1, further supporting the classification of the fluid collected as normal lymphatic fluid. 25,26…”
Section: Discussionmentioning
confidence: 99%
“…Other studies noted that the appearance of fluid and volume of chest-drain output alone lack sensitivity and specificity for detection of chylous leakage, and they occasionally integrated physical and biochemical analysis of chyle into their management of diagnosis. 2,36 Until the findings of this study, we used 200 mL of chesttube output as the cutoff to remove the chest tube, and we did not take body weight into account. When we retrospectively evaluated our data, we found that patients' chest-tube output per kg body weight correlated well with clinical outcome and necessary treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoprotein electrophoresis, which identifies chylomicrons, remains the gold standard to confirm the diagnosis of chylothorax in pleural fluid. However, lipoprotein electrophoresis is no longer performed in most laboratories, but could provide important information for the diagnosis in difficult cases (9 ). In our case, the appearance of a white ring at the top of the pleural fluid sample after 12 h at 4°C confirmed the presence of chylomicrons.…”
Section: Discussionmentioning
confidence: 50%